Practical design strategy for two-phase step up DC-DC fibonacci switched-capacitor converter - Wong, Yan Chiew; Zhou, Wei; El-Rayis, Ahmed O.; Haridas, Nakul; Erdogan, Ahmet T.; Arslan, Tughrul S. (2011)
The Fibonacci Switched-Capacitor (SC) converter demonstrates the highest performance by using minimum number of capacitors. However, as the Fibonacci SC requires a wide range of voltage rating of the devices, its implementation is difficult. This paper presents two gate driving techniques for designing and implementing two-phase Fibonacci SC converter for both low and high step-up conversion ratios. The proposed gate driving techniques only require few auxiliary transistors to provide the required boosted voltages for turning the charge transfer switches in the converter on and off. As a result, the proposed gate driving techniques reduce the design complexity and increase the reliability of the Fibonacci SC converter. Practical 8X and 5X Fibonacci SC converters are simulated and constructed based on the proposed techniques. The high conversion efficiencies achieved prove the effectiveness of the proposed techniques.